Engineering students can use the words “calculus” and “love” in the same sentence: using active learning the impossible can happen - Cuzzuol, Gilberto Duarte (2018)
Teaching Calculus can be one of the most challenging practices in the engineering context for a number of reasons, namely: taught at the beginning of engineering courses, introducing to the student in a critical phase of his/her transition between high school and university, not understanding the meaning of some contents in relation to Engineering. The disciplines of Calculus are responsible for high failure rates and students’ dropout. Lectures are predominantly used to teach Calculus in engineering context, with rigid contents centered on the blackboard and in the book. Therefore, students have low interaction with teachers and they have difficult to build their own knowledge and to understand the importance of mathematical methods, and procedures. However, project based learning was used to teach Calculus to engineering students. Students were asked to choose a phenomenon of their Engineering area of knowledge and explain why and how it needs integrals and derivatives to be explained. 127 students from six engineering courses were involved in the experiment. The students were organized in teams and tutored by other professors. This paper aims to describe the experience and analyze the outcomes terms of the perception of learning and development of transversal competences. The evaluation was based on content analysis of the reports delivered by the students. 100% of the groups evaluated the experience as positive. The students used adjectives such as "excellent", "extraordinary" to characterize the experience. In addition, students reported the following learning outcomes: knowledge and understanding; analysis; problem-solving; creativity/originality; communication and presentation; evaluation; planning and organization; interactive and group competences. Some groups reported that, in this project, they created prototypes that they will keep on researching and developing to take these ideas to the market. Yet, in this experience, the failure rate of this discipl